MobileMonday culture : the lure of participatory space - Pineda, Roger (2010)
This master’s thesis explores participatory culture’s social logic and its manifestations in social media. It employs the case study method to examine participatory culture’s patterns of interaction through the experiences of participants in Mobile Monday, a global community sharing common professional interests in mobile communications. It provides an historical perspective on the technology and concepts used in social media, and applies a theoretical framework based on the premise of participatory culture as a manifestation of the postmodern condition, influenced by tacit aesthetics, and dominated by media culture. The framework includes aesthetic strategies related to social media and the elements of social media. The case study addresses questions concerning the relationships between social media’s elements, and how they affect innovation and collective ideology. The study indicates social media usage generates possibilities to gain knowledge and social capital for a larger portion of a participatory community, beyond the control of a select group. It indicates that sharing a common ideology and aesthetic of collectivity promotes a common identity among members of the Mobile Monday community, but their dynamic could also fragment the communal identity. Conclusions from the study imply the need for a strategy of transition to social media sites in order to take full advantage of the potential values, and the need for an understanding of the dynamic and aesthetic of identity fragmentation in participatory cultures such as Mobile Monday to help participants plan for and mitigate conflicts that arise amongst groups with diverse experiences and diverse approaches to creative agency, and exploit their diverse experiences in order to promote cooperation and generate innovations.